Further development of the Affordances for Motor Behavior of Schoolchildren: standardized version and scoring system - Fábio Saraiva Flôres; Luis Paulo Rodrigues; Rita Cordovil (Revista Brasileira de Atividade Física e Saúde)
Mapping and evaluating regular contexts that schoolchildren attend is of great importance to understanding motor behavior. This communication aims to present the scoring system and standardization of the Affordances for Motor Behavior of Schoolchildren (AMBS), recently presented to the scientific and educational community. The AMBS was developed to assess children’s interdependent systems, such as home, school, and sports activities, that can influence 6 to 10-year-olds’ motor development, motor learning, and motor competence. The questionnaire was completed by 377 Brazilian families. Raw scores of each of the three subscales (home, materials, and school) were transformed into standard scores, ranging from very low to very high. AMBS subscales were classified as very low (1st quartile), low (2nd quartile), good (3rd quartile), and very good (4th quartile). The AMBS total raw score is a result of the sum of the three subscales standard scores and can be classified into three categories, ranging from a low to a high AMBS. Thus, AMBS total scores were classified as low (1st tercile), average (2nd tercile), and high (3rd tercile). We expect that raw and standard scores of the AMBS can be used by researchers, parents, and clinical/education professionals to assess children’s affordances for motor behavior.